NANOENCAPSULATED ESSENTIAL OILS: TRENDS, INVESTMENTS, AND APPLICATIONS IN COSMETOLOGY (REMUNOM, 2025)
Nanotechnology, by manipulating materials at the nanometric scale, has revolutionized various sectors, with notable applications in the cosmetic industry, particularly in enhancing essential oils. This study examines the implications of this technology on the production chain, with a focus on the Brazilian context. Nanotechnology endows materials with unique properties, such as greater chemical reactivity and efficacy, which has driven global investment in research and development (R&D). While countries like the United States, the European Union, and Japan lead these investments, Brazil, albeit on a smaller scale, has allocated significant resources, such as the R$89.5 billion directed to science and technology in 2019. In the cosmetic sector, nanotechnology enables the creation of innovative products, such as nanocosmetics, which incorporate essential oils to enhance benefits like hydration, anti-aging effects, and antimicrobial properties. Companies like L'Oréal, O Boticário, and Natura already market such products, demonstrating market viability and acceptance. The demand for natural and sustainable ingredients has expanded the use of essential oils, such as Tea Tree and Lavender, in cosmetic formulations, with thousands of patents registered globally. In conclusion, nanotechnology not only enhances product quality and efficacy but also aligns with sustainability and innovation trends, establishing itself as a transformative pillar in the cosmetic industry and in the valorization of natural resources like essential oils.